Caring for people God's way : personal and emotional issues, addictions, grief, and trauma - Clinton, Timothy E., 1960-; Hart, Archibald D.; Ohlschlager, George W., 1951- (Nashville : Nelson Reference & Electronic, 2005)
Publisher description: Caring for People God's Way presents Christian counseling in a systematic, step-by-step manner that outlines the process as practically as possible. It then applies the process to the most common issues faced by Christian counselors: personal and emotional issues, trauma, grief, loss, and suicide.
Introduction to Christian counseling : the 21st-Century state of the art / Tim Clinton and George Ohlschlager -- The person and the counselor : growing in knowledge, character, and skill / Tim Clinton, George Ohlschlager, and Anthony J. Centore -- Christian counseling and essential biblical principles / Ian Jones, Tim Clinton and George Ohlschlager -- Christian counseling process : goals, traits, stages, and plan / George Ohlschlager and Tim Clinton -- Christian counseling ethics : honoring a clear moral structure / George Ohlschlager and Tim Clinton -- Helping people forgive : getting to the heart of the matter / E.L. Worthington Jr. -- Depression and bipolar disorders / Siang-Yang Tan and Michael Lyles -- Stress and anxiety / Archibald Hart and C. Hart Weber -- Perfectionism and obsessive-compulsive disorders / Mark E. Crawford -- Managing your anger / Gary J. Oliver and Carrie E. Oliver -- Personality disorders / Henry A. Virkler -- Addictions / Mark R. Laaser, George Ohlschlager and Tim Clinton -- Sexual addiction / Mark R. Laaser -- Gambling, spending, and credit abuse / Gregory L. Jantz -- Eating disorders / Linda S. Mintle -- Suicide intervention / George Ohlschlager, Mark Shadoan, and Gary Stewart -- Loss and grief work / Sharon Hart May -- Trauma and PTSD : a clinical overview / Michael Lyles, Tim Clinton, and Anthony J. Centore -- Adult survivors of sexual abuse : trauma, treatment, and living in the truth / Diane Langberg -- Abortion : crisis decision and post-abortion syndrome / Theresa Burke, Tim Clinton and George Ohlschlager.
"A joint publication and service ministry of the AACC and Thomas Nelson publishers" -- t.p.
Includes bibliographical references (p. [509]-528) and index.
Keywords: Pastoral counseling; Church work with the mentally ill; Counseling -- Religious aspects -- Christianity; Caring -- Religious aspects -- Christianity